Economic overview of a two-agent process for underground coal gasification with Fischer–Tropsch-based poly-generation. Issue 1 (27th February 2019) - Brand, Johan F; Van Dyk, Johan C; Waanders, Frans B
Abstract: Underground Coal Gasification (UCG) is a mining-gasification process that produces synthesis gas from in situ coal by injecting air (or oxygen and steam) and extracting the produced gas via boreholes. The resulting synthesis gas ('syngas') produced by UCG can be used directly as a fuel-gas or deep-cleaned to produce many other products like chemicals, liquid fuels, hydrogen and synthetic natural gas. UCG has significant environmental, safety and practical advantages over conventional coal mining and utilization, foremost being cost and emissions reductions. In South Africa, facilities of an industrial-scale Fischer–Tropsch (FT) have been operating for decades on coal-to-liquid and gas-to-liquid conversion. Oxygen-blown UCG produces syngas, which contains a mixture of carbon monoxide (CO) and hydrogen, and these molecules can be conditioned to serve as feed for synthetic-crude-oil ('syncrude') conversion technologies based on the FT process. African Carbon Energy (Pty) Ltd. ( Africary ) completed a study integrating its UCG technology with mini gas-to-liquids plant. Syngas from Africary's Theunissen Underground Coal Gasification (TUCG) project will be used for power production and synthesis of liquid fuels in a unique poly-generation configuration. The TUCG process will consist of two parallel gasifiers, operated on different agents, making the component parts of UCG and coal-to-(any product) (CtX) tightly linked and interdependent, but reducing both cost and emissions. UCG-CtX offers a lower capital investment to conventional underground mining and surface gasification due to the removal of the surface gasifier and coal-mine operations. The gas clean-up systems will remove undesirable components from each gasifier and blend the cleaned syngas for H2 :CO ratio control and provide implementation of carbon capture and sequestration. This study has minimized the complexity and optimized the process flow to provide own-use electricity and about 4000 barrels/day equivalent fuels at a capital cost estimate (2017) of about US$ 350 million and operating cost of around 28 US$/barrel.